Comparison of the performance of an organic acid and an inorganic acid pretreatment by means of enzymatic hydrolysis of coffee husk - Castro-Ferro, Nataly Alejandra; Maniak, Halina (European Journal of Chemistry, 2023)
The study of different lignocellulosic materials for second-generation biofuels is one of the trending topics today because of the high demand for fuels for transportation and electricity generation. Coffee husk is presented as one study option considering that only 10% of the coffee fruit is used for coffee production. The pretreatment of the coffee husk with sulfuric acid (3 or 6%) and citric acid (6 or 12%) was compared using two methodologies. The first had reaction condition time (50, 70, 90, and 1440 min) and temperature (70 and 90 °C), while the second had autoclave conditions (121 °C, 14.696 psi, 60 min). The comparison was made to find the best methodology for acid pretreatment before enzymatic hydrolysis. The best result of the reduction of sugars (17.017%) and glucose yield (3.882%) was found with 6% C6H8O7 in autoclaving (121 °C, 14.696 psi, 60 min) with hydrolysis conditions of 72 h, 150 rpm, 50 °C, and using cellulases from Trichoderma reesei.